2015
DOI: 10.1016/j.jams.2014.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Laser Acupuncture for Treating Musculoskeletal Pain: A Systematic Review with Meta-analysis

Abstract: Laser acupuncture has been studied extensively over several decades to establish evidence-based clinical practice. This systematic review aims to evaluate the effects of laser acupuncture on pain and functional outcomes when it is used to treat musculoskeletal disorders and to update existing evidence with data from recent randomized controlled trials (RCTs). A computer-based literature search of the databases MEDLINE, AMED, EMBASE, CINAHL, SPORTSDiscus, Cochrane Library, PubMed, Current Contents Connect, Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 71 publications
2
53
3
3
Order By: Relevance
“…However, after discussion with a biostatistician, it was suggested that 17 participants were appropriate for such a preliminary feasibility study. This study did not follow up participants beyond 3 months postrandomization; in accordance with previous studies [20,21], a longer term follow-up may show favorable effects of LLLT (PBM) over BCRL conventional therapy. This thus supports the need for the main trial to assess outcome measures in the long-term follow-up (!6 months post-treatment) [27].…”
Section: Discussionsupporting
confidence: 77%
“…However, after discussion with a biostatistician, it was suggested that 17 participants were appropriate for such a preliminary feasibility study. This study did not follow up participants beyond 3 months postrandomization; in accordance with previous studies [20,21], a longer term follow-up may show favorable effects of LLLT (PBM) over BCRL conventional therapy. This thus supports the need for the main trial to assess outcome measures in the long-term follow-up (!6 months post-treatment) [27].…”
Section: Discussionsupporting
confidence: 77%
“…[6][7][8][9][10][11] There is also moderate to strong empirical evidence for other interventions for chronic pain, such as yoga, 12 massage therapy, 13,14,15 , and CBT. 16 There is some limited support for other NPTs such as acupuncture 17,18,19 and Tai Chi. 20,21 The research on TENS is inadequate to make recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Laser acupuncture (LA) is a noninvasive, painless alternative to needles using low-level intensity light. There is evidence for use in myofacial pain [4,36] and numerous other conditions [4]. In children, LA reduces intensity and number of migraine headaches [23], decreases vomiting in post-operative settings [51], and reduces duration of morphine therapy and hospital stay in neonatal abstinence syndrome infants [44].…”
Section: Introductionmentioning
confidence: 99%